2000
DOI: 10.1007/s001340000716
|View full text |Cite
|
Sign up to set email alerts
|

Low flow inflation pressure-time curve in patients with acute respiratory distress syndrome

Abstract: Provided that constant flow is given relatively fast, P-T accurately determines the shape of P-V, as well as the LIP and UIP. Flow delay causes a leftward shift of the initial part of P-T, masking the presence of LIP and UIP in some cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
4
0
5
Order By: Relevance
“…Although the mechanism improving hypoxemia is not clear, it is thought that synchrony between patient respiration and mechanical ventilation will be improved to change lung compliance and gas exchange for the better. Also, the mechanism is thought to reduce barotrauma and atelectasis in expiration by controlling inhaled air volume and pressure in lung inflammatory reaction, consequently resulting in the reduction of lung and systemic inflammations 107 . Although it can be expected that the duration of mechanical ventilation will be increased because of weakened neural muscles due to neuromuscular blockage, the meta-analysis showed that it was not different from the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism improving hypoxemia is not clear, it is thought that synchrony between patient respiration and mechanical ventilation will be improved to change lung compliance and gas exchange for the better. Also, the mechanism is thought to reduce barotrauma and atelectasis in expiration by controlling inhaled air volume and pressure in lung inflammatory reaction, consequently resulting in the reduction of lung and systemic inflammations 107 . Although it can be expected that the duration of mechanical ventilation will be increased because of weakened neural muscles due to neuromuscular blockage, the meta-analysis showed that it was not different from the control group.…”
Section: Resultsmentioning
confidence: 99%
“…3) [27,28]. Analyzing P/t curves using a classical sigmoidal equation [22] enables the shape, LIP, and UIP to be accurately determined and yields results comparable to those obtained with traditional pressurevolume curves.…”
Section: Reproducibility Of Pressure-volume Curvesmentioning
confidence: 74%
“…(55,68) Ο Lu και συν εισήγαγαν µία απλή µέθοδο καταγραφής της καµπύλης P-V σε ένα αναπνευστικό κύκλο (µέθοδος χορήγησης χαµηλής εισπνευστικής ροής ). (70) Σε µία πρόσφατη µελέτη έχουµε δείξει ότι κάτω από ειδικές συνθήκες η καµπύλη P-T που καταγράφετε µε αυτή τη µέθοδο είναι ταυτόσηµη µε την αντίστοιχη καµπύλη P-V. (91) Η καταγραφή της καµπύλης P-T µπορεί να γίνει εύκολα στην οθόνη παρακολούθησης των ασθενών µε µόνο επιπλέον εξοπλισµό ένα µορφοµεατροπέα πίεσης. (91) Σκοπός αυτής της εργασίας ήταν η µελέτη των µεταβολών στις µηχανικές ιδιότητες Η καταγραφή της καµπύλης πίεσης-όγκου (P-V) έγινε µε τη µέθοδο της χορήγησης χαµηλής εισπνευστικής ροής µε προσαρµογή των παραµέτρων µε βάση τις τεχνικές δυνατότητες του αναπνευστήρα που χρησιµοποιήθηκε στη µελέτη.…”
Section: εισαγωγηunclassified
“…(70) Σε µία πρόσφατη µελέτη έχουµε δείξει ότι κάτω από ειδικές συνθήκες η καµπύλη P-T που καταγράφετε µε αυτή τη µέθοδο είναι ταυτόσηµη µε την αντίστοιχη καµπύλη P-V. (91) Η καταγραφή της καµπύλης P-T µπορεί να γίνει εύκολα στην οθόνη παρακολούθησης των ασθενών µε µόνο επιπλέον εξοπλισµό ένα µορφοµεατροπέα πίεσης. (91) Σκοπός αυτής της εργασίας ήταν η µελέτη των µεταβολών στις µηχανικές ιδιότητες Η καταγραφή της καµπύλης πίεσης-όγκου (P-V) έγινε µε τη µέθοδο της χορήγησης χαµηλής εισπνευστικής ροής µε προσαρµογή των παραµέτρων µε βάση τις τεχνικές δυνατότητες του αναπνευστήρα που χρησιµοποιήθηκε στη µελέτη. (70) Συγκεκριµένα πριν την έναρξη της καταγραφής και προκειµένου το αναπνευστικό σύστηµα να είναι σε θέση ισορροπίας πριν την έναρξη της καταγραφής της καµπύλης, για 5 αναπνοές, οι συνθήκες αερισµού καθορίζονταν σε: V T 0.5-0.6 L µε σταθερή ροή, f 10 /λεπτό και σχέση (Τ Ι /Τ ΤΟΤ ) 0.3.…”
Section: εισαγωγηunclassified
See 1 more Smart Citation